OF RENT COLLECTORS AND DEBT COLLECTORS - Henk Delport (Obiter, 2023)
This note examines the question whether an estate agent collecting or receiving monies in the course of his or her business as an estate agent is also a “debt collector” as defined in the Debt Collectors Act 114 of 1998. The matter is of some importance: if the answer is in the affirmative it would mean that estate agents mandated to collect rentals, levies or other monies payable in terms of sale or lease transactions must register with both the Estate Agency Affairs Board (“the Board”) in terms of the Estate Agency Affairs Act 112 of 1976 and the Debt Collectors Council (“the Council”) in terms of the Debt Collectors Act. They will have to pay levies to both the Board and the Council and comply with the codes of conduct published by both statutory bodies. Improper professional conduct may lead to disciplinary action instituted by either the Board or the Council, or both. They will have to open and keep two trust accounts (one in terms of s 32 of the Estate Agency Affairs Act and the other in terms of s 20 of the Debt Collectors Act) and will often be confused as to which monies must be paid into which of these accounts.